The innovation of the courses management system - Ab. Rahman, Azwana; Sahak, Mohd Dasuki; Mohd Kamal, Nurdiyana; Mohamad Kasim, Suzaini (Universiti Teknologi MARA, Kedah, 2019)
PSAS has started organizing fee-based courses since 2010 in order to generate some income for the library. This is in line with the University's goal to generate at least 30% from the operational budget. Prior to the innovation, courses management was conducted manually since 2010 and the number of courses organized was limited. At the beginning of 2018, the KPI for income generation from courses has been raised up as to generate more revenue for PSAS. In order to achieve this KPI, PSAS should increase the numbers of courses organized and promote widely to get more participants. Hence, PSAS found that the manual method of managing the courses can no longer be ble to accommodate the workloads. Innovation of Course Management System was introduced to replace the previous work system and was fully implemented since January 2018 by using Google Apps; and free apps. This innovation has successfully facilitated management of course and through this innovation, 10 courses have been successfully organized in the year 2018 and generated over RM50, 000.00. This amount is 400% higher than the income generated in the previous year. For January until May 2019, eight courses were organized with the income over RM45, 000.00. PSAS has many advantages such as easy to build and use, integrates with other applications, and have the potential to be developed by other organizations. For example, a workshop on online registration form was conducted in March 2019 and successfully attracted participants from other libraries. Moreover, this innovation has been recognised as an innovative projects in UPM during the “Service Quality and Innovation Day UPM 2018” by winning second place for the Service Innovation Award (Management Category).